Observations of near-bottom currents in Bornholm Basin, Slupsk Furrow and Gdansk Deep. (June 2016) - Bulczak, A.I.; Rak, D.; Schmidt, B.; Beldowski, J.
Abstract: Dense bottom currents are responsible for transport of the salty inflow waters from the North Sea driving ventilation and renewal of Baltic deep waters. This study characterises dense currents in three deep locations of the Baltic Proper: Bornholm Basin (BB), Gdansk Basin (GB) and Slupsk Furrow (SF). These locations are of fundamental importance for the transport and pollution associated with chemical munitions deposited in BB and GB after 2nd World War. Of further importance the sub-basins are situated along the pathway of dense inflowing water.Current velocities were measured in the majority of the water column during regular cruises of r/v Oceania and r/v Baltica in 2001–2012 (38 cruises) by 307 kHz vessel mounted (VM), downlooking ADCP. Additionally, the high-resolution CTD and oxygen profiles were collected. Three moorings measured current velocity profiles in SF and GB over the summer 2012. In addition, temperature, salinity, oxygen and turbidity were measured at about 1 m above the bottom in GB. The results showed that mean current speed across the Baltic Proper was around 12 cm s −1 and the stronger flow was characteristic to the regions located above the sills, in the Bornholm and Slupsk Channels, reaching on average about 20 cm s −1 . The results suggest that these regions are important for the inflow of saline waters into the eastern Baltic and are the areas of intense vertical mixing. The VM ADCP observations indicate that the average near-bottom flow across the basin can reach 35±6 cm s −1 . The mooring observations also showed similar near-bottom flow velocities. However, they showed that the increased speed of the near-bottom layer occurred frequently in SF and GB during short time periods lasting for about few to several days or 10–20% of time. The observations showed that the bottom mixed layer occupies at least 10% of the water column and the turbulent mixing induced by near-bottom currents is likely to produce sediment resuspension and transport within the layer in all three sub-basins. The turbidity measurements, performed for 5-month-long time period over the summer 2012 in GB show that increased sediment resuspension is associated with a faster near-bottom flow.